Effect of Binder Content on the Erosive Wear of Ti(C, N)‐Based Cermet in SiO2 Particle‐Containing Simulated Seawater. Issue 6 (17th October 2013) - Guo, Zhixing; Xiong, Ji; Wan, Weicai; Dong, Guangbiao; Yang, Mei
<x xml:space="preserve">Abstract</x> Erosion of Ti(C, N)‐10 wt% Mo2C‐15 wt% Ni/Co cermet of different Ni/Co in artificial seawater containing 5 wt% SiO2 was investigated. Pure Ni‐bonded cermet exhibited the largest wear rate of 35.7*10−3 mm3/h, which decreased to 17.7*10−3 mm3/h with the substitution of 30% Ni by Co. Further decrease of Ni/Co ratio resulted in the improvement of erosion resistance. Pure Co binder resulted in the increase hardness from 92.0 to 92.5 HRA and transverse rupture strength from 1510 to 1650 MPa. The erosion resistance was slightly worse due to an increasing hardness and brittleness of the binder phases, but the hard phases still kept the as‐prepared morphology.